ANALISIS KEAUSAN DAN KOEFISIEN GESEK MENGGUNAKAN TRIBOMETER PIN ON DISC PADA BAJA AISI C1045 DENGAN VARIASI KETEBALAN COATING GSLS NANO CERAMIC - Irwan Ardiyatna; Althesa Androva, Aan Burhanuddin (ADISAM PUBLISHER, 2024)
Pin-on-disc is a tool component of a tribometer that is used to test or determine the wear and friction values of a material object. Pin-on-disc consists of a ball-shaped pin and a disc-shaped disc made of steel (Prabowo et al, 2012). The research aims to determine the comparison of wear and friction levels of AISI C1045 steel material using a variety of coatings, namely without coating, half coating, one layer of coating, and 2 layers of coating. The highest wear value lies in the 2nd layer coating variation with a wear value of 59.985 gr/s.mm2. while the lowest wear value lies in the variation of without coating, namely -19.13 gr/smm2. Meanwhile, in the friction coefficient comparison, the highest value occurred in the one layer coating variation, namely 0.46, and the lowest geek coefficient value occurred in the 2 layer coating test, namely -0.481. The conclusionfrom these results is that variations in coating thickness will affect the wear rate of the disc material. It can be seen from the data that has been obtained that the 2 layer coating variation has a very high wear value compared to other variations.